Sequestered Evidence and the Distortion of Clinical Practice Guidelines - McGoey, L (2009)
As a result of the growth of evidence-based practices across the world, health-care providers and policymakers in the United States, United Kingdom, and Europe have established institutes such as the United Kingdom’s National Institute for Health and Clinical Excellence (NICE) to produce clinical guidelines that physicians are asked to use in their daily practice. This article discusses how the withholding of clinical trial information by pharmaceutical companies and academic researchers affects the reliability of clinical guidelines. It first offers a case study analysis of the U.K. drug regulator’s failure to prosecute GlaxoSmithKline, manufacturer of the bestselling antidepressant Seroxat (manufactured as Paxil in North America), for withholding information on the safety of Seroxat from regulators. It next examines the idea of a “Sarbanes- Oxley for Science,” a recent proposal that seeks to introduce legislation forcing companies to disclose clinical trials that have indeterminate or negative results. Legislation such as Sarbanes-Oxley for Science would solve some problems with the withholding of data, but not all. Until practitioners and policymakers address the political and legal barriers preventing full access to clinical trial data for all medical treatments, the ideals of evidence-based practice will remain elusive.